Peran Transformasi Kurikulum dalam Meningkatkan Kinerja Kepala Sekolah: Kajian Literatur dalam Konteks Pendidikan Indonesia - Norsiva, Norsiva; Hermina, Dina (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2025)
The purpose of this study is to examine the effects of curriculum transformation on Indonesian school administrators' work habits. Based on research, it is believed that school administrators who are able to comprehend and effectively explain curriculum changes can improve their leadership effectiveness and the school's operational efficiency. Successful curriculum transformation requires school administrators to have a thorough understanding of new curriculum and strong managerial skills to facilitate changes and communicate with all stakeholders in the school. This study indicates that school administrators who practice participative leadership can help teachers adopt innovative teaching strategies and create productive work environments. In addition, effective communication with teachers, students, and other staff members is crucial to ensuring successful curriculum implementation. This gives the impression that in order to achieve curriculum transformation, cooperation between the school principal, the teacher, and other important people is required. Because of this, the study suggests that education should focus more on increasing the capacity of the school principal to deal with constantly changing curriculum.